Pengembangan Perangkat Pembelajaran Gerak Dasar Lari Berbasis Aplikasi Articulate Storyline - Yuliansyah, Achmad Rizal; Wiguno, Lokananta Teguh Hari; Kurniawan, Ari Wibowo; Mu’arifin, Mu’arifin (Sport Science and Health, 2021)
Abstract: The purpose of this research is to develop basic motion learning tools for running based on the articulate storyline application. In the analysis technique carried out in this study using quantitative descriptive analysis using percentages. test results by learning experts get a percentage of 94%, elementary school game expert test results get a percentage of 96%, validation tests by Physical Education, Sports and Health experts get a percentage of 90%, media expert test results get a percentage of 96 %, the athletic expert test results get a percentage of 93%, the test results in the small group get a percentage of 89% and the large group test results get a percentage of 86%, and that means the overall test results by several experts as well as product tests for small groups and large groups in the product development of basic motion learning tools for running based on the articulate storyline application has very valid criteria and is suitable for use. It can be concluded that the product of developing basic motion learning tools for running based on the articulate storyline application is feasible to use and can be used as a learning support for the subject of Physical Education, Sports and Health in grade IV SD for basic motion learning material for running. Abstrak: Tujuan dari penelitian ini yaitu untuk mengembangkan perangkat pembelajaran gerak dasar lari berbasis aplikasi articulate storyline. Pada teknik analisis yang dilakukan dalam penelitian ini menggunakan analisis deskriptif kuantitatif menggunakan persentase. hasil uji oleh ahli pembelajaran mendapatkan hasil persentase sebesar 94%, hasil uji ahli permainan Sekolah Dasar mendapatkan hasil persentase sebesar 96%, uji validasi oleh ahli Pendidikan Jasmani, Olahraga dan Kesehatan diperoleh hasil persentase sebesar 90%, hasil uji ahli media mendapatkan hasil persentase 96%, hasil uji ahli atletik mendapatkan hasil persentase 93%, Hasil uji pada kelompok kecil diperoleh persentase 89% dan hasil uji  kelompok besar diperoleh persentase sebesar 86%, dan artinya keseluruhan hasil uji oleh beberapa ahli serta uji produk untuk kelompok kecil dan kelompok besar pada produk pengembangan perangkat pembelajaran gerak dasar lari berbasis aplikasi articulate storyline mendapatkan kriteria sangat valid dan layak digunakan. Maka dapat disimpulkan bahwa produk pengembangan perangkat pembelajaran gerak dasar lari berbasis aplikasi articulate storyline ini layak digunakan dan dapat dijadikan sebagai penunjang pembelajaran pada mata pelajaran Pendidikan Jasmani Olahraga dan Kesehatan kelas IV SD untuk materi pembelajaran gerak dasar lari.